DIPLOMASI PANDA SEBAGAI DIPLOMASI PUBLIK TIONGKOK TERHADAP JEPANG - Darmawan, Aulia Surya Putri; Damayanti, Christy; Haqqi, Halifa (Solidaritas, 2020)
This research is to explain and analysis about panda diplomacy as China’s public diplomacy toward Japan. This research reviewed by using public diplomacy theory and bilateral relation theory. This research is to find out how panda diplomacy as China’s public diplomacy toward Japan. This method used qualitative descriptive method. From this analysis, the researcher find out that panda diplomacy as China’s public diplomacy can attract society and Japan’s medias. China’s panda diplomacy able to influenced and create awareness of fauna preservation in Japan society by establishing The Panda Protection Institute of Japan which is a private non-government voluntary organization in Japan. PPIJ can be strengthen of bilateral relations between China and Japan. Keywords: Panda diplomacy, Public Diplomacy, Bilateral Relation